JMP Volume I Nomor 1 Edisi Desember 2011 - Redaksi JMP (Jurnal Maksipreneur, 2011)
The Journal of Maksipreneur (JMP) is a periodical scientific journal published by the Faculty of Economics, Universitas Proklamasi 45 (UP45) Yogyakarta, Indonesia, twice a year. This journal is intended to collect any summary of research results, scientific development writings, book reviews, as well as original ideas are fresh and challenging related to the study of development in management, cooperatives, and entrepreneurship. The editors invite academicians, researchers, and practitioners who have a great interest in the development of scholarship in these fields to submit their best work.